VD_FINDINFO HC / 2025 / 682 vom 1. Januar 2021 - VD Tribunal cantonal (2021)
RÉCUSATION, EXPERT, FRAIS D'EXPERTISE | 183 al. 2 CPC (CH), 319 let. a CPC (CH), 319 let. b CPC (CH), 47 al. 1 let. f CPC (CH)